Strain and strain rate echocardiography for evaluation of right ventricular dysfunction in patients with idiopathic pulmonary arterial hypertension - Filusch, Arthur; Mereles, Derliz; Grünig, Ekkehard; Buß, Sebastian Johannes; Katus, Hugo; Meyer, Franz Joachim (Clinical research in cardiology, 2010)
Optimizing the non-invasive imaging of right ventricular (RV) function is of increasing interest for therapy monitoring and risk stratification in patients with idiopathic pulmonary hypertension (IPAH). Therefore, this study evaluated strain and strain rate echocardiography as a tool for comprehensive assessment of RV function and disease severity in IPAH patients. In 30 IPAH patients [WHO functional classes II-IV; mean pulmonary artery pressure (mPAP) 48.8 ± 12.5 mmHg; pulmonary vascular resistance (PVR) 7.9 ± 5.3 Wood units] and in 10 matched healthy control subjects’ two-dimensional echocardiography, 6-MWD and N-terminal pro-brain natriuretic peptide (NT-proBNP) levels were obtained. In IPAH patients when compared with controls, RV systolic strain (−18.8 ± 4.3 vs. −34.5 ± 3.8%, p = 0.0016) and strain rate (−1.6 ± 0.6 vs. −2.7 ± 0.5 s−1, p = 0.018) were significantly altered and correlated significantly with elevated NT-proBNP levels (r = 0.73 and r = 0.62; p < 0.001, respectively) and reduced 6-MWD (r = −0.76 and r = −0.81; p < 0.001). In IPAH patients, reduced strain correlated with both mPAP (r = 0.61, p = 0.01 for strain; and r = 0.55, p = 0.04 for strain rate, respectively), and PVR (r = 0.84, p < 0.001 for strain; and r = 0.67, p < 0.001 for strain rate, respectively). This study gives first comprehensive evidence that strain echocardiography allows accurate non-invasive assessment of RV function and disease severity in patients with IPAH.
Gesehen am 24.04.2023